Rare but Possible: Three Roots with Three Canals in Maxillary First Premolars in Pakistani Subpopulation - Shaher Bano; Malik Adeel Anwar; Khadija Arif; Rai Sadaf Nawaz; Annam Aziz; Fatima Khalil (Pakistan Journal of Medicine and Dentistry)
Background: The anatomical complexity of maxillary first premolars in root and canal configurations can present challenges in endodontic treatment and extractions. Maxillary first premolars may occasionally have three roots and three canals, affecting treatment outcomes. Therefore, this study was designed to assess the variations in the number of roots and root canals in maxillary first premolars in the Pakistani subpopulation using Cone Beam Computed Tomography.